Public Preferences For Implementation of Sharia Hotel Facilities - Euis Puspita Dewi; Sularso Budilaksono; Febrianty Febrianty; Fahrul Nurzaman; Ahmad Rosadi (Universitas Pendidikan Indonesia, 2022)
A b s t r a c tThe purpose of this study is to investigate people's preferences for the use of sharia concepts in the provision of sharia hotel services. When not all of the sharia criteria are met, the community's preferences become extremely significant in determining the priorities that sharia hotel managers can satisfy in offering amenities that meet the sharia idea. This study used a quantitative descriptive method, using online surveys distributed to 109 community respondents in Indonesia. Respondents were chosen using convenience sampling and given a questionnaire with closed questions based on five sharia hotel facility requirements. This research resulted three major priorities selected by the respondents: 1) the selection of guests who come to stay and restrictions on visiting guests, 2) the provision of facilities for worship and purification as well as providing a religious atmosphere, 3) arrangement of male and female visitors in supporting facilities such as entertainment, fitness and swimming pools.A b s t r a kPenelitian ini bertujuan untuk menggali preferensi masyarakat mengenai penerapan konsep syariah dalam penyediaan fasilitas hotel syariah. Ketika belum semua kriteria syariah mampu diterapkan, preferensi masyarakat menjadi sangat penting untuk menentukan prioritas yang dapat dipenuhi oleh pengelola hotel syariah dalam menyediakan fasilitas yang memenuhi konsep syariah. Studi ini menggunakan metode deskriptif kuantitatif dengan menyebarkan kuesioner secara online pada 109 responden masyarakat di Indonesia. Responden dipilih dengan menggunakan convenience sampling dan diberikan kuesioner dengan pertanyaan tertutup, berdasarkan 5 kriteria fasilitas hotel syariah. Hasil penelitian ini menunjukkan bahwa terdapat 3 prioritas utama yang dipilih oleh responden: 1) pemilihan tamu yang datang menginap dan pembatasan tamu yang berkunjung, 2) penyediaan fasilitas untuk beribadah dan bersuci serta memberikan suasana religi, 3) penataan pengunjung pria dan wanita di fasilitas penunjang seperti hiburan, fitnes dan kolam renang.